Learning Network Services for Professional Development - Koper, Rob (Springer Berlin Heidelberg : Imprint: Springer, 2009)
A "Learning Network" is a community of people who help each other to better understand and handle certain events and concepts in work or life. As a result - and sometimes also as an aim - participating in learning networks stimulates personal development, a better understanding of concepts and events, career development, and employability. "Learning Network Services" are Web services that are designed to facilitate the creation of distributed Learning Networks and to support the participants with various functions for knowledge exchange, social interaction, assessment and competence development in an effective way. The book presents state-of-the-art insights into the field of Learning Networks and Web-based services which can facilitate all kinds of processes within these networks. The main emphasis of the contributions is to explain what services a Learning Network requires and what the reader should do to design and run Learning Network Services, including guidelines on how to evaluate the effectiveness of these services. This book is a rich source of information for practitioners and professional developers who want to stimulate learning by professionals through web-based social interaction. Managers of educational institutions and training companies will find many ideas about possible services to offer. At the same time, it is an excellent introduction for other researchers in the field, and for students interested in the learning sciences or technology-enhanced learning.